(untitled) - Tolkien, J. R. R. (New york, 1987)
To protect a magic ring, Frodo, the hobbit, must undertake a long and dangerous journey
Keywords: Magicians,Fantasy fiction, English,Phù thủy,Pháp sư,Tiểu thuyết viễn tưởng Anh,Wizards; Drama,Phim,Phim,Drama